European University Initiative in the context of digital transformation: A discussion paper - Morawska, Joanna; Carayannis, Elias G. (Quaestiones Geographicae, 2024)
The digital transformation (DT) has undoubtedly become one of the main challenges of modern organisations, including universities. The discussion is oriented towards the new learning tools, contexts, needs and skills needed on the institutional level, academic teachers and in connection to the demands of the labour market. This paper does not refer to potential ethical and safety risks but rather tries to understand how universities should approach those challenges from the perspective of their key missions, including education as a top priority. To do that, we use the example of the concept of the European University Initiative (EUI) case, as it has become one of the flagship programmes of the European Commission supporting the European Higher Education Area (EHEA) and European Research Area (ERA). With the purpose to build inter-university campuses, joint degree programmes, support seamless mobility, strengthen socially relevant research, promote sustainability etc., they also have become the lighthouses of the green and digital transformations. In this paper we aim to start a discussion about what digital transformation means in the context of teaching and try to define the most urgent questions that will help to define the future university model responding to the dynamically changing learning context.